2020
DOI: 10.1002/jac5.1348
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy student perception of a remote hypertension and drug information simulation‐based learning experience in response to the SARS‐CoV‐2 pandemic

Abstract: IntroductionSevere acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) has required pharmacy educators to redesign or create new simulation‐based learning (SBL) activities to ensure achievement of accreditation standards and ensure practice‐ready pharmacists. Little is known regarding student perception of SBL activities conducted across the Doctor of Pharmacy (Pharm.D.) curricula during the SARS‐CoV‐2 pandemic.ObjectiveTo assess first‐year Pharm.D. students' confidence in performing manual blood pressure te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Included studies represented 14 different countries. There was a North American predominance to authorship, with 30 studies featuring authors located in the United States 17–46 and 5 studies included authors from multiple countries 23,27,47–49 Figure 2. highlights the reported origins of all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included studies represented 14 different countries. There was a North American predominance to authorship, with 30 studies featuring authors located in the United States 17–46 and 5 studies included authors from multiple countries 23,27,47–49 Figure 2. highlights the reported origins of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, less than half of the included studies were found to have a low risk of bias (n = 27/54, 49%) as seen in Appendix B (Table, Supplemental Digital Content 2, http://links.lww.com/SIH/A983). Of the 16 studies that were evaluated with the NIH assessment tool (NHBLI, NIH) for prestudies and poststudies with no control group, 18,19,21,22,26,29,33,34,36,38,47,49,53–56 more than half were assessed to be at low risk for bias (n = 9/16, 56%) 21,26,29,33,34,36,38,47,54 . Twenty-eight studies additionally were evaluated using the appropriate CASP tools 17,20,23,25,27,30–32,35,37,39,40,43,44,46,48,50–52,55,57–64 .…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacy Education 24(1) 91 -145 100 popular for improving self-perception of interprofessional competence and attitude toward interprofessional collaboration (in 9 articles) (Koo et al, 2014;Shrader et al, 2015;Shrader et al, 2016;Ottis & Gregory, 2016;Iverson et al, 2018;Patel et al, 2018;Curley et al, 2019;Cowart & Updike, 2021). The SBIRT (Screening, Brief Intervention and Referral to Treatment) tool helped students collaborate to identify potential medication misuses (Marken et al, 2010;MacDonnell et al, 2016;Clauser et al, 2020;Egelund et al, 2020;Acquavita et al, 2021).…”
Section: Non-virtual Simulation Training In Pharmacy Education: a Sco...mentioning
confidence: 99%
“…Some barriers to interprofessional education were eliminated thanks to a telehealth simulation, particularly during the Covid-19 pandemic. In this way, the telehealth simulation was able to improve the student's confidence in the use of these technologies (Estes et al, 2016;Begley et al, 2019;Wen et al, 2019;Ma et al, 2020;Cowart & Updike, 2021;Wong et al, 2021;Baalmann et al, 2023). Incorporating telehealthlearning into a curriculum may give students an opportunity to be better prepared to practice in the ever-evolving healthcare environment (Estes et al, 2016).…”
Section: Implications Of Simulation Training In Hmmentioning
confidence: 99%